A low complexity partial transmit sequence approach based on hybrid segmentation scheme - Ali Hussein Fadel; Hasanain H. Razzaq; Salama A. Mostafa (Institute of Advanced Engineering and Science, 2020)
The partial transmit sequences (PTS) is regarded as a promising scheme for inhibiting ‎the high peak-to-average power ratio (PAPR) problem in the orthogonal frequency division ‎multiplexing (OFDM) systems. The PTS scheme relies on partitioning the ‎data sequence into subsets and weighting these subsets by a group of the phase rotation ‎factors. Although the PTS can efficiently reduce the high PAPR value, a great ‎computational complexity (CC) level restricts the utilization of the PTS scheme in practical ‎applications. In PTS, there are three common types of segmentation schemes; ‎interleaving (IL-PTS), pseudo-random (PR-PTS), and adjacent (Ad-PTS) schemes. This ‎paper presents a new algorithm named hybrid pseudo-random and interleaving cosine wave shape ‎‎(H-PRC-PTS) by combining the PR-PTS scheme and the symmetrical ‎interleaving cosine wave shape (S-IL-C-PTS) scheme which was proposed in our previous ‎work. The results indicate that the suggested algorithms can ‎diminish the PAPR value like the PR-PTS scheme, whereas the CC level is reduced significantly.